17-Allylamino-demethoxygeldanamycin Used Alone or in Combination with Sodium Orthovanadate Promotes Apoptosis and Inhibits Invasion of SH-SY5Y Cells by Modulating PIWIL2. (21st November 2020) - Tian, Xiaohong; Wei, Wumei; Wang, Xiaohong; Ao, Qiang; Fan, Jun; Hou, Weijian; Bai, Shuling; Tong, Hao
Abstract : Neuroblastoma (NB) is one of the most common extracranial solid tumors of childhood and accounts for 15% of cancer deaths. Even with the multimodality treatment protocols, the advanced-stage tumor overall 5-year survival rate is less than 50%. Therefore, novel drug therapy targeting cellular signal transduction pathways regulating the apoptotic cascade may be important for the treatment of drug-resistant NB. In our previous studies, we have demonstrated that 5 μ M sodium orthovanadate (SOV) induced the apoptosis of SH-SY5Y cells. 17-Allylamino-demethoxygeldanamycin (17-AAG) is a geldanamycin- (GA-) derived heat shock protein 90 (Hsp90) inhibitor, and it has been shown to have potent antitumor activity in head and neck cancers. However, the effect of 17-AAG on the apoptosis of NB cells has not been reported. Therefore, the purpose of this study was to determine the effects of 17-AAG and SOV on the growth and invasion of SH-SY5Y cells in vitro and explore the related mechanism. In this study, we first investigated the antiviability effect of 17-AAG on SH-SY5Y cells, then studied the cell apoptosis and invasion influenced by 17-AAG and SOV, and assessed the role of PIWI-Like2 (PIWIL2) and piRNA-PIWI signaling in it. The results showed that 5 μ M 17-AAG inhibited cell growth and viability and induced apoptosis in SH-SY5Y cells. Both 17-AAG and SOV reduced the level of PIWIL2 and Bcl-xl proteins and inhibited the invasion of SH-SY5Y cells. In addition, the combined use of the two drugs had greater effect than the single use of any drug.